NEEDS ANALYSIS IN DEVELOPING E-LKPD BASED ON GENIALLY EDUCATIONAL GAMES IN MATHEMATICS LEARNING TO INCREASE LEARNING MOTIVATION - Rohmah, Indah Ainur; Fatmawati, Erma; Usriyah, Lailatul (Attadib: Journal of Elementary Education, 2024)
AbstractThis study aims to analyze the needs of developing E-LKPD based on Genially educational game in learning mathematics for grade III students at SDIT Ar-Rahmah Yosowilangun. The analysis stages include curriculum, learner, and teacher needs, as well as solution analysis. The research method used is the ADDIE model (Analysis, Design, Development, Implementation, Evaluation) with data collection techniques through observation and interviews. The subjects of this study were third grade students of SDIT Ar-Rahmah Yosowilangun. The results showed that there is a clear need for the development of E-LKPD based on Genially educational game in learning grade III mathematics, due to the low motivation of students to learn. Analysis of curriculum needs indicates the need for innovative approaches to improve the quality of mathematics learning in accordance with the demands of the Merdeka Curriculum. The analysis of learners highlights the internal and external factors that influence their interest in mathematics, while the analysis of teachers shows the need for support and facilitation in developing innovative learning materials. Thus, this study suggests the need for the development of E-LKPD based on the Genially educational game as a solution to increase the learning motivation of grade III students. By utilizing technology and interactive learning approaches, it is expected to create a dynamic and interesting learning environment for students. In addition, the results of this study can be the basis for developing learning strategies that are more effective and relevant to the needs of students in today's digital era.Keywords; E-LKPD, Educational Games, Genially, Mathematic LearningAbstrakPenelitian ini bertujuan untuk menganalisis kebutuhan pengembangan E-LKPD berbasis game edukasi Genially dalam pembelajaran matematika untuk peserta didik kelas III di SDIT Ar-Rahmah Yosowilangun. Tahapan analisis meliputi kebutuhan kurikulum, peserta didik, dan guru, serta analisis solusi. Metode penelitian yang digunakan adalah model ADDIE (Analysis, Design, Development, Implementation, Evaluation) dengan teknik pengumpulan data melalui observasi dan wawancara. Subjek penelitian ini adalah peserta didik kelas III SDIT Ar-Rahmah Yosowilangun. Hasil penelitian menunjukkan bahwa terdapat kebutuhan yang jelas untuk pengembangan E-LKPD berbasis game edukasi Genially dalam pembelajaran matematika kelas III, karena rendahnya motivasi belajar peserta didik. Analisis kebutuhan kurikulum mengindikasikan perlunya pendekatan inovatif untuk meningkatkan kualitas pembelajaran matematika sesuai dengan tuntutan Kurikulum Merdeka. Analisis terhadap peserta didik menyoroti faktor-faktor internal dan eksternal yang memengaruhi minat mereka terhadap matematika, sementara analisis terhadap guru menunjukkan kebutuhan akan dukungan dan fasilitasi dalam pengembangan materi pembelajaran yang inovatif. Dengan demikian, penelitian ini menyarankan perlunya pengembangan E-LKPD berbasis game edukasi Genially sebagai solusi untuk meningkatkan motivasi belajar peserta didik kelas III. Dengan memanfaatkan teknologi dan pendekatan pembelajaran yang interaktif, diharapkan dapat menciptakan lingkungan pembelajaran yang dinamis dan menarik bagi peserta didik. Selain itu, hasil penelitian ini dapat menjadi dasar bagi pengembangan strategi pembelajaran yang lebih efektif dan relevan dengan kebutuhan peserta didik di era digital saat ini..Kata kunci; E-LKPD, Game Edukasi, Genially, Pembelajaran Matematika